2014
DOI: 10.17761/ijyt.24.1.u7747w56066vq78u
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Integrative Restoration-Yoga Nidra Meditation (iRest®) to Women with Sexual Trauma at a Veteran's Medical Center: A Pilot Study

Abstract: Objective: This pilot study examines iRest, a form of guided mindfulness meditation, and its ability to reduce symptoms associated with sexual trauma, including military sexual trauma (MST), in a sample of women seeking psychotherapy services at a Department of Veterans Affairs (VA) medical center. Methods: 90-minute sessions were held 19 times, twice a week for 10 weeks, except for the week with a holiday. Participants completed self-report measures Brief Symptom Inventory-18 (BSI), Posttraumatic Cognitions I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…47 In a study delivering iRest to women with sexual trauma, the program was found to decrease body tension and improve overall quality of sleep. 16,48 Pain severity improved in our study as well, trending toward significance. Other iRest studies have also found improvements in pain.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…47 In a study delivering iRest to women with sexual trauma, the program was found to decrease body tension and improve overall quality of sleep. 16,48 Pain severity improved in our study as well, trending toward significance. Other iRest studies have also found improvements in pain.…”
Section: Discussionsupporting
confidence: 68%
“…14 Small pilot studies with veterans have shown reduced rage, anxiety, and emotional reactivity; increased feelings of relaxation, peace, self-awareness, and self-efficacy 15 ; and significantly decreased depression, increased feelings of joy, and improved quality of sleep and ability to manage stress. 16 Although significant positive preliminary data have been collected on iRest, no studies have evaluated its ability to reduce depression symptoms in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…16 Yoga nidra diminished stress and anxiety levels significantly 80 college students Military combat veterans reported alleviation of post-traumatic stress disorder (PTSD) symptoms like rage and anxiety and increased feelings of relaxation and peace after yoga nidra as a therapy. 13,17,18 The study revealed significant improvement in anxiety scores after six months of intervention with Yoga Nidra in intervention group in comparison to control group. Previous studies have also shown significant reduction in the quality anxiety scores following meditation and breathing exercises.…”
Section: Benefits Of a Yoga Nidramentioning
confidence: 86%
“…11 Other pilot studies, with veterans, have shown reduced rage, anxiety, and emotional reactivity; increased feelings of relaxation, peace, self-awareness, and self-efficacy 15 ; and significant d e c reases in depression, increased feelings of joy, and improved quality of sleep and ability to manage stress. 16 In a 2017 pilot study, we evaluated iRest for older adults with depression. 12 In a controlled trial, generally healthy adults, aged 55-90, with depression symptoms were randomized to receive a 2-day retreat of either iRest meditation training or vacation at EarthRise Retreat Center in Petaluma, California.…”
Section: Introductionmentioning
confidence: 99%